UMPSA establishes China-Malaysia Regional Vocational Skills Centre to offer Mandarin language courses with vocational skills - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 4 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has established the China–Malaysia Chinese Plus Vocational Skills Regional Development Center (Malaysia), a regional centre for vocational skills development through a formal collaboration between UMPSA, the Center for Language Education and Cooperation (CLEC), and Hebei University.